Result of depression screening among elderly residents [Bi̇r huzurevi̇nde depresyon taramasi sonuçlari] - (:unkn) unknown (My University, 2006)
Background and Aim: Psychosocial and functional losses which accompany aging frequently may lead to depression. However, many elderly patients who have depressive symptoms do not present with these symptoms to health-care system. In this study, we aimed to screen elderly patients living in a residential house, for depression and its relation to a few factors. Material and Methods: We have taken a detailed medical history and physical examination of 39 elderly living in a residency house. We also have administered a functional evaluation. We administered Yessevage Depression Scale to all 39 residents. We also administered WHO-Quality of Life Scale-Breef to all residents. Results: 23 (%67) of the residents that we have interviewed were women, 13 (%33) were men. Mean (SD) age was 82.6(7.45). According to Yessevage scale; 8(%20.5) of them had a depression scale score (DSS) higher than cut-off point 13. There were no relationship between age, sex, inappropriate medication use, activities of daily living scale results and depression. Higher DSS were more frequent among the elderly who had a lower education level. There was also statistically significant relationship between quality of life scale psychological scores and DSS. Conclusion: A primary care physician should always keep in mind that unrecognised depression may be quite common among elderly perople and depression should be screened amongst the elderly.
Keywords: Activities of daily living; Elderly depression; Quality of life; Screening